2000
DOI: 10.1046/j.1442-9071.2000.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐incubation of Acanthamoeba castellanii with strains of Pseudomonas aeruginosa alters the survival of amoeba

Abstract: Enhanced survival of Acanthamoeba castellanii has previously been reported following co-incubation with a single strain of Pseudomonas aeruginosa. The aim of this study was to evaluate the impact of different strains of P. aeruginosa on amoebae survival. Four contact lens solutions were challenged with A. castellanii for between 6 and 24 h, and survival rates of amoeba were calculated. Subsequently, A. castellanii was co-incubated with different strains of P. aeruginosa (strain 6294, an invasive isolate; 6206,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 13 publications
0
18
0
2
Order By: Relevance
“…Previously, it was assumed that Pseudomonas aeruginosa and Acanthamoeba were mutually exclusive ocular pathogens, since Pseudomonas expressed amoebicidal activity in co-cultivation 36. More recently, in vitro studies have showed that Pseudomonas can actually cooperate in the pathogenesis of contact lens related AK: in fact, it increases the resistance of Acanthamoeba to contact lens disinfecting solutions and creates a biofilm on contact lenses surface that enhances amoebae retention 37 . Pseudomonas-Acanthamoeba co-infections have also been described in keratitis patients, along with the presence of Pseudomonas aeruginosa intracellularly in environmental Acanthamoebae 20, 38…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was assumed that Pseudomonas aeruginosa and Acanthamoeba were mutually exclusive ocular pathogens, since Pseudomonas expressed amoebicidal activity in co-cultivation 36. More recently, in vitro studies have showed that Pseudomonas can actually cooperate in the pathogenesis of contact lens related AK: in fact, it increases the resistance of Acanthamoeba to contact lens disinfecting solutions and creates a biofilm on contact lenses surface that enhances amoebae retention 37 . Pseudomonas-Acanthamoeba co-infections have also been described in keratitis patients, along with the presence of Pseudomonas aeruginosa intracellularly in environmental Acanthamoebae 20, 38…”
Section: Discussionmentioning
confidence: 99%
“…associated with keratitis (Elder et al, 1994;Hay et al, 1994;Seal et al, 1996;Kim & Hahn, 1999). However, very low concentrations of PHMB (0.00005%), polyaminopropyl biguanide (0.00005%) and the QAC polyquaternium-1 (0.055-0.001%) were reported to be inactive against A. castellanii (Penley et al, 1989;Davies et al, 1990;Silvany et al, 1990;Zanetti et al, 1995;Cengiz et al, 2000), A. polyphaga (Penley et al, 1989;Davies et al, 1990;Silvany et al, 1990) and A. culbertsoni (Connor et al, 1991). Several investigations showed that the concentration of polymeric biguanides in multipurpose solutions commercially available was not cysticidal within the manufacturer's recommended contact time (Buck et al, 1998;Kilvington, 1998;Niszl & Markus, 1998).…”
Section: Activity Of Cationic Biocidesmentioning
confidence: 99%
“…The external bacteria enhance the growth and binding of Acanthamoeba trophozoites to contact lenses, and also enhance the survival of amoeba in biocidal lens care solution (Cengiz et al, 2000). However, the mechanisms by which bacteria affect the virulence and pathogenicity of Acanthamoeba infections have yet to be thoroughly elucidated.…”
mentioning
confidence: 99%